Ernest A. Moody, Studies in Medieval Philosophy. Science and Logic (Collected Papers 1933-1969), University of California Press, Berkeley (Cal.), 1975, XX + 454 pp. - Argerami, Omar (1977)
Fil: Argerami, Omar. Investigador Independiente; Argentina